Risk perception and mental health among college students in China during the COVID-19 pandemic: A moderated mediation model - Li, Ling; Cao, Hua; Yang, Ling; Yan, Changhu; Wang, Xinru; Ma, Yanhong (Frontiers in Psychiatry, 2022)
Since the outbreak of the COVID-19 epidemic, it has spread on a large scale around the world, seriously affecting people's physical and mental health. In China, almost all schools have postponed semesters, suspended offline classes, and implemented closed-off management, which has brought significant challenges to the study and life of college students. The study aimed to explore the relationship between risk perception, perceived stress, perceived control, and mental health among Chinese college students. This cross-sectional study was conducted among 1856 college students. The results showed that risk perception was positively correlated with mental health. After adding the mediating variable of perceived stress, risk perception still significantly predicted mental health. In addition, the interaction term of perceived stress and perceived control significantly negatively predicted mental health. Specifically, perceived stress significantly affected mental health in the low-perceived control group. In contrast, in the high-perceived control group, the predictive effect of perceived stress on mental health disappeared. The present study showed that perceived stress partially mediated the relationship between risk perception and mental health; perceived control moderated the relationship between perceived stress and mental health, and high perceived control could buffer the effect of perceived stress on mental health.